Thermoluminescence and glow curves analysis of γ-exposed Eu3+ doped K3Y(PO4)2 nanophosphors. (January 2016) - Gupta, Palvi; Bedyal, A.K.; Kumar, Vinay; Singh, Vivek K.; Khajuria, Y.; Ntwaeaborwa, O.M.; Swart, H.C.
Graphical abstract: Highlights: First time, a detailed comparative study of the glow curves and kinetic parameters was made on K3 Y(PO4 )2 nanophosphor. Combustion method was employed to synthesize the Eu 3+ doped K3 Y(PO4 )2 nanophosphor. The nanophosphor exhibited sublinear response suggesting that it is suitable for TL dosimetry. Abstract: Eu 3+ doped K3 Y(PO4 )2 nanophosphor was synthesized by combustion synthesis using urea as a fuel. The crystal structure and particle morphology of the nanophosphor were investigated by using X-ray diffraction and transmission electron microscopy, respectively. A Thermoluminescence (TL) study was carried out after exposing the samples to gamma radiation. The TL glow curves exhibited a prominent peak at 407 K and a small hump at 478 K. The intensity of the peaks increased with the increase in the dose of the gamma rays (0.01–5 kGy). The K3 Y(PO4 )2 : Eu 3+ (2.5 mol%) nanophosphor exhibited sublinear TL response to γ-radiation over a wide range of gamma doses (0.01–5 kGy). The TLanal program was used to analyze the glow curves of the K3 Y(PO4 )2 nanophosphor at different doses (0.2–5 kGy) and different heating rates (3–10 K/s). A comparative study was done for kinetic trapping parameters that were determined by the peak shape methods of Chen, Grossweiner and Lushchik. The frequency factors (s) for each glow peak were also calculated. The values of the activation energy ( E ) obtained by the TLanal program were in good agreement with those obtained by the peak shape methods. The effect of different amount of doses and different heating rates are discussed.